RISK FACTORS FOR LIPID METABOLISM DISORDERS OF DIFFERENT GENESIS OF ORIGIN (LITERATURE REVIEW) - Mavlonov N.H. (Scholar Express Journals, 2023)
Lipid metabolism disorder is a condition characterised by disturbance of the ratio of atherogenic and non-atherogenic lipoproteins, which tends to develop in modern society. In modern medicine it is proved that dyslipidemias include a wide range of disorders, and they have a leading role in the development of cardiovascular and neurological diseases with severe complications. This factor alone or in combination with other factors creates the risk of atherosclerosis. In recent years, much attention has been paid to the detection and treatment of elevated total cholesterol (TC) and LDL-C. However, other forms of dyslipidaemia have also been shown to cause disease
Keywords: hyperlipidaemia; dyslipidaemia; pathogenesis; complications